“THINK FAST, ACT SMART" PROBLEM BASED LEARNING IN ELT: CASE STUDY OF TEACHERS PROFESIONAL DEVELOPMENT - Hayati Nupus; Teguh Kurniyanto; Regina Delviani Putri; Veniati (Cakrawala Pedagogik, 2026)
Problem-Based Learning (PBL) as an alternative learning method that can provide students with the knowledge and experience to work independently in constructing their own knowledge. This study aims to improve the conceptual understanding of Pamulang University management students on the topic of oral and written recount texts through the application of the Problem-Based Learning model. The study was conducted from December to January 2026, with 30 students from classes 03MJSP001, 03MJSP005, 01MJSP001, and 01MJSP003, and four lecturers of varying gender and age. The study used a qualitative case study with a cycle approach, each cycle going through five stages of activity: Planning, Implementation, Action, Observation, and Reflection. The results of this study indicate: Based on the results of the study, there was an increase in learning motivation in four classes, with an average of 70.50 in cycle I and 82.00 in cycle II. Before learning with the Problem Based Learning (PBL) Learning Method, the student's score was 66.50. In the first cycle, the results of student evaluations in the English subject of oral and written text material in the form of recounts got an average score of 70.50, while in the second cycle, the average score was 82.00. From this study, there was an increase in learning completeness of 75% in the first cycle and 95% in the second cycle. Thus, it can be concluded that the implementation of the Problem Based Learning (PBL) Learning Method for English learning on oral and written text material in the form of recounts can improve the English learning outcomes of Pamulang University management students. The conclusion of the study is that the application of the Problem Based Learning model can improve students' conceptual understanding of the subject of oral and written texts in the form of recounts.